The Influence of Destination Attribute on Behavior Intention through Memorable Tourist Experience and Tourist Satisfaction as Intervening Variables - eny endah pujiastuti; Hastho Joko Nur Utomo; Laila Mawadatul Imtikhanah; Dyah Widowati; Muhammad Rizki Firdaus (University of Merdeka Malang, 2023)
The current shift in tourist travel trends is witnessing a transition from mass tourism to alternative tourism, emphasizing natural and cultural experiences aimed at enhancing insight, adventure, and learning. This shift encompasses activities such as adventure tourism, mountain climbing, trekking, and village tourism, offering direct experiences to tourists (Coordinating Ministry for Maritime Affairs and Investment, 2021). The Jenissari tourist village distinguishes itself by offering life packages as its primary attraction. The research aims to investigate the impact of destination attributes on various aspects of tourist experiences and behaviors. Specifically, it explores the influence of destination attributes on memorable tourist experiences, tourist satisfaction, and behavioral intentions. The study was conducted in the tourist village of Jenissari, Sleman, DIY, with a sample comprising tourists who have visited and availed the life package. Data was collected using Google Forms, resulting in 128 effective questionnaires, which were then analyzed using Structural Equation Modeling (SEM) through the AMOS application. The findings indicate that destination attributes significantly affect memorable tourist experiences, tourist satisfaction, and behavioral intentions. Additionally, the study reveals the mediating role of memorable tourist experiences and tourist satisfaction in the relationship between destination attributes and tourist behaviors.